Failure Mode of Tunnel Face Under Transient Unsaturated Seepage with Temperature Influence - Yi Xie; De Zhou; Hong Liao; Jianqun Zhu (Mathematics)
The seepage caused by heavy rainfall and storm runoff is not a static phenomenon. On the contrary, it is a dynamic process known as unsaturated transient seepage. Under the condition, the spatiotemporal variations in suction stress cannot be overlooked. With the development of tunnel mechanics, there has been an emergence of tunnels affected by high ground temperatures or temperature influences, highlighting the necessity of incorporating temperature effects into the analysis. This article proposes a new framework for the spatiotemporal response of tunnel face safety to temperature-affected and unsaturated transient seepage conditions. A one-dimensional transient seepage assumption is used to develop an analytical model describing unsaturated transient seepage, which is then integrated centered on suction stress strength theory for unsaturated soils to acquire suction stress variations with depth and time. The temperature impact on the unsaturated soil shear strength is incorporated, applying a temperature-sensitive effective stress model in conjunction with the soil–water characteristic curve to quantitatively analyze temperature-induced apparent cohesion changes. The 3D logarithmic spiral failure model is used to analyze the tunnel face stability. The validity of the proposed failure model is demonstrated through an engineering calculation. The rates of internal dissipation and external work are calculated, and a kinematic approach related to strength reduction is used to determine the safety factor of the tunnel face with zero support pressure. The results show that considering transient unsaturated seepage and temperature effects can increase the safety factor. The influence of these effects mainly depends on the soil type, tunnel geometric parameters, and seepage conditions. This work explores the influence of variations in a series of parameters on the failure mode of tunnel faces under temperature effects, taking into account unsaturated transient seepage, thereby providing valuable references for the design and construction of tunnels in the future.